The Foundation of Academic Excellence and Student Achievement Based on Qur'anic Tahfid: Pondasi Keunggulan Akademis dan Prestasi Siswa Berbasis Qur’anic Tahfid - Wijiyono, Eko; Tobroni, Tobroni; Widodo, Joko (Academia Open, 2025)
General background: Memorization of the Qur’an (Qur’anic Tahfid) is a central practice in Islamic education that extends beyond religious devotion to cognitive and emotional development. Specific background: Previous studies suggest that Qur’anic Tahfid fosters memory, discipline, and motivation, which are essential for academic excellence. Knowledge gap: However, the relationship between psychological conditions and the effectiveness of Qur’anic Tahfid remains underexplored, with limited empirical evidence connecting memorization practices to academic achievement in modern educational contexts. Aims: This study aims to analyze the influence of Qur’anic Tahfid on students’ academic performance by reviewing indexed scientific literature published between 2020–2025. Results: Findings indicate a significant positive correlation between Qur’anic memorization and academic outcomes, where students excelling in Tahfid consistently demonstrate superior performance in other subjects, supported by enhanced memory control, discipline, and emotional regulation. Novelty: This research highlights Qur’anic Tahfid as not only a spiritual practice but also a pedagogical strategy that strengthens cognitive functions and psychological resilience. Implications: Integrating Qur’anic Tahfid into formal curricula provides a holistic educational approach that promotes intellectual, emotional, and moral development, positioning it as a foundation for academic excellence and lifelong learning. Highlights: Qur’anic Tahfid enhances memory, discipline, and motivation. Strong correlation exists between Tahfid and academic achievement. Integration into curricula supports holistic student development. Keywords: Qur’anic Tahfid, Academic Excellence, Cognitive Development, Emotional Regulation, Holistic Education